Implementation of Multiple Intelligences Determinant Applications for Junior High School Students Using Web-Based Likert Scale Method - Aris Tri Jaka Harjanta; Rahmat Robi Waliyansyah; Zainal Arifin (Universitas Islam Sultan Agung, 2022)
Multiple intelligences or commonly called multiple intelligences are various skills and talents that students have to solve various problems in learning. The problem in this research is how is the process of developing applications for determining multiple intelligences for junior high school students using the method web-based Likert scale?, how is the feasibility of the application for determining multiple intelligences for junior high school students using the web-based Likert scale method?, and how is the effectiveness of using the application for determining multiple intelligences for junior high school students using the web-based Likert scale method?. In the development of this web-based application system using the PHP programming language and MySQL database. This type of research is research and development (R&D) with the Likert scale method. With a population of 21 students of SMP Negeri 2 Sayung Demak and a sample of 21 students of class VIII F. Based on the User Acceptance Test for students, it produced a number of results covering several aspects, namely in terms of usability, in terms of convenience and in terms of appearance, it produced an average percentage of 84%. These results are included in the criteria for strongly agree.